Reanalysis of Ωc→Ξc+K- Decay in QCD. (10th May 2018) - Aliev, T. M.; Bilmis, S.; Savci, M.
Abstract : The strong coupling constants of newly observed Ω c 0 baryons with spins J = 1 / 2 and J = 3 / 2 decaying into Ξ c + K - are estimated within light cone QCD sum rules. The calculations are performed within two different scenarios on quantum numbers of Ω c baryons: (a) all newly observed Ω c baryons are negative parity baryons; that is, the Ω c ( 3000 ), Ω c ( 3050 ), Ω c ( 3066 ), and Ω c ( 3090 ) have quantum numbers J P = 1 / 2 - and J P = 3 / 2 - states, respectively; (b) the states Ω c ( 3000 ) and Ω c ( 3050 ) have quantum numbers J P = 1 / 2 - and J P = 1 / 2 +, while the states Ω c ( 3066 ) and Ω c ( 3090 ) have the quantum numbers J P = 3 / 2 - and J P = 3 / 2 +, respectively. By using the obtained results on the coupling constants, we calculate the decay widths of the corresponding decay. The results on decay widths are compared with the experimental data of LHC Collaboration. We found out that the predictions on decay widths within these scenarios are considerably different from the experimental data; that is, both considered scenarios are ruled out.